Serum Bilirubin Associated with Stroke Severity and Prognosis: Preliminary Findings on Liver Function after Acute Ischemic Stroke. (2nd January 2023) - Duan, Honglian; Cheng, Zhe; Yun, Ho Jun; Cai, Lipeng; Tong, Yanna; Han, Zhenzhen; Geng, Xiaokun; Ding, Yuchuan
ABSTRACT: Objective: This study investigates relationships between serum bilirubin, stroke severity, and prognosis of patients with acute ischemic stroke (AIS) to elucidate the roles of the liver in AIS. Methods: This retrospective study collected data from 527 patients diagnosed with AIS within 24 hours after their symptom onset. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS). Mild stroke was defined as NIHSS≤5. Prognosis was assessed with modified Rankin Scale (mRS) on 90 days after AIS and good prognosis was defined as mRS≤2. The patients were divided based on their total bilirubin (Tbil) and direct bilirubin (Dbil) levels to study these serum markers' association with the severity of stroke. Tbil levels were measured and compared with mRS on 90 days to analyze prognosis of mild stroke patients. Results: Both Tbil abnormal (NIHSS = 6.8 ± 5.3) and Dbil abnormal groups (NIHSS = 7.3 ± 5.7) had higher NIHSS scores on admission than the normal groups ( p < 0.05 or p < 0.01, respectively). Severity of stroke at discharge was similar between these groups ( p = 0.025 and 0.019, respectively). Serum bilirubin levels were independently associated with stroke severity on admission and discharge after risk factors were adjusted ( p < 0.001 and p < 0.05, respectively; β (95%CI) were 0.116 (0.064–0.167) and 0.058 (0.012–0.103), respectively). The average Tbil levels of mild stroke with good prognosis was 15.1 ± 6.4umol/l versus 11.8 ± 3.1umol/l with poor prognosis; this difference was statistically significant ( p = 0.003). The same difference was observed with Dtil levels but it did not reach a significant level. Conclusion: High Tbil and Dbil level within 48 hours of symptom onset could be an independent marker of severity of stroke on admission and discharge for all AIS patients. For patient with mild stroke, elevation of bilirubin after AIS suggests a good prognosis. These findings imply that the liver play the key roles in the mechanism of AIS.